2000
DOI: 10.1128/jcm.38.9.3420-3428.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of the Capsule Gene Cluster (cps) in Nontypeable Group B Streptococci Reveals Two Majorcps Allelic Variants of Serotypes III and VII

Abstract: Forty group B Streptococcus (GBS) isolates obtained from Europe and the United States previously reported to be nontypeable (NT) by capsule serotype determination were subjected to buoyant density gradient centrifugation. From nearly half of the isolates capsule-expressing variants could be selected. For characterization of the remaining NT-GBS isolates, the capsule operon (cps) was amplified by the long-fragment PCR technique and compared by restriction fragment length polymorphism (RFLP) analysis. The patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The first step in the investigation of the molecular basis for the loss of capsule expression in Streptococcus agalactiae was the selection of a wide panel of strains devoid of capsule. GBS serotyping by Lancefield immuno-precipitation or by latex agglutination can indeed provide discrepant results regarding the NT phenotype [ 28 , 29 ]. To investigate capsule expression by a more accurate flow-cytometry based approach, we generated monoclonal antibodies against purified CRM-conjugated polysaccharides of the five most frequent capsular genotypes, i .…”
Section: Resultsmentioning
confidence: 99%
“…The first step in the investigation of the molecular basis for the loss of capsule expression in Streptococcus agalactiae was the selection of a wide panel of strains devoid of capsule. GBS serotyping by Lancefield immuno-precipitation or by latex agglutination can indeed provide discrepant results regarding the NT phenotype [ 28 , 29 ]. To investigate capsule expression by a more accurate flow-cytometry based approach, we generated monoclonal antibodies against purified CRM-conjugated polysaccharides of the five most frequent capsular genotypes, i .…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that the insertion of IS1548 immediately upstream of the laminin binding gene lmb , was associated with an ~5-fold increase both in the transcription of lmb , and in the phenotypic bacterial adhesion to laminin 38 . Conversely, insertion of IS1548 into the hylB and cpsD genes, abrogated the production of hyaluronidase and bacterial capsule, respectively 37 , 39 . Of note, IS1548 has also been documented in the covRS -system in S. pyogenes .…”
Section: Discussionmentioning
confidence: 99%
“…Most NT isolates express surface proteins: alpha and beta components of the C protein or one or more of the R protein antigens, Rib, and Alp1-4 proteins (Benson et al, 2002;Kong et al, 2002b). These isolates can be genotyped and distinguished by PFGE and by the expressed surface-protein antigens Sellin et al, 2000). The C proteins were recognized by Lancefield as protective determinants found in GBS of serotypes Ia and Ib (reviewed by Lindahl et al, 2005).…”
Section: Introductionmentioning
confidence: 99%